Evaluation of stable reference genes for RT-qPCR analysis in Antheraea assamensis (Lepidoptera: Saturniidae) during pathogenic infections - Indumathi Kamatchi Balakrishnan; Himanshu Dubey; Pawan Shukla; Rajal Debnath; C. Vanitha; Gangavarapu Subrahmanyam; Manthira moorthy; Kallare P. Arunkumar; Vikram Kumar; Abhishek Singh; K. M. Ponnuvel (Molecular Biology Reports, 2025)

Effect of hybrid fiber and hybrid rebars on flexural strength of reinforced concrete beams - R. Rajkumar; Abhay Yadav; C. Arunkumar (Innovative Infrastructure Solutions, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

First report of leaf spot disease on Zanthoxylum rhetsa caused by Fusarium solani-melongenae in India - N. Surmina Devi; T. Shantibala; Arunkumar Phurailatpam; N. Y. Chanu; Anju Choudhury; Priyanka Irungbam; P. Raja; R. C. Shakywar (Indian Phytopathology, 2025)

Study on cyclic behavior of concrete column steel beam connections - Madhu Paudel; C. Arunkumar; R. Rajkumar (Innovative Infrastructure Solutions, 2024)

Morpho-physiological analysis of salinity tolerance in sugarcane genotypes - Kumar Preet; Pooja Dhansu; Nirmala Sehrawat; Ravinder Kumar; C. Appunu; Krishnapriya Vengavasi; Raja Arunkumar; Rohit Rana; Surender Kumar; Vikas Joon (Plant Physiology Reports, 2024)

Greening the oil industry: Microalgae biorefinery for sustainable oil-produced water treatment and resource recovery - Mohammad Sibtain Kadri; Nayana K.; Reda Fassi Fihri; Gholamreza Abdi; Sukumar C.; Arunkumar Kulanthaiyesu (Journal of Water Process Engineering, 2024)

Feasibility of bioplastic production using micro- and macroalgae- A review - Muthiyal Prabakaran Sudhakar; Rahulkumar Maurya; Sanjeet Mehariya; Obulisamy Parthiba Karthikeyan; Gopal Dharani; Kulanthiyesu Arunkumar; Sandra V. Pereda; María C. Hernández-González; Alejandro H. Buschmann; Arivalagan Pugazhendhi (Environmental Research, 2024)

Current approaches, and challenges on identification, remediation and potential risks of emerging plastic contaminants: A review - Huy Hoang Phan Quang; Duc Anh Dinh; Vishal Dutta; Ankush Chauhan; Sudip Kumar Lahiri; C. Gopalakrishnan; Arunkumar Radhakrishnan; Khalid Mujasam Batoo; Lan-Anh Phan Thi (Environmental Toxicology and Pharmacology, 2023)

Seismic performance of steel frame equipped with structural fuse - C. Arunkumar; N. Umamaheswari (Innovative Infrastructure Solutions, 2023)

Doppler indices of uterine arteries and mRNA transcripts of hormone receptors in cervix vis-à-vis dilatation therapy in buffaloes affected with incomplete cervical dilatation associated with uterine torsion - Ravjibhai K. Chaudhari; Tarunkumar V. Sutaria; Arunkumar C. Patel; Chandrakant F. Chaudhari (Animal Reproduction Science, 2023)

Molecular epidemiology of enteroviruses associated with hand, foot, and mouth disease in South India from 2015 to 2017 - Ramachandran Erathodi Sanjay; Joseph Josmi; Sarita Sasidharanpillai; Sheik Shahin; C. J. Michael; Sasidharanpillai Sabeena; S. Aswathyraj; Karunakaran Kavitha; Cheerngod Shilpa; S. Varamballi Prasada; Jayaram Anup; Govindakarnavar Arunkumar (Archives of Virology, 2022)

Characterization of Power Ultrasound Modified Kappaphycus alvarezii Biosorbent and its Modeling by Artificial Neural Networks - Sumit Kumar; S. Nisanth Manokar; Nirmal Thirunavookarasu; V. Nivethitha; T. N. Nidhusri; T. Niranjana; C. K. Sunil; S. Vignesh; Arunkumar Anandharaj; Ashish Rawson (Water, Air, & Soil Pollution, 2022)

Numerical study on the behaviour of resilient beam-column end plate connection with dual structural fuse - C. Arunkumar; N. Umamaheswari (Innovative Infrastructure Solutions, 2022)

Correction to: Hyperglycaemia cause vascular inflammation through advanced glycation end products/early growth response-1 axis in gestational diabetes mellitus - Barathi Rajaraman; Nirupama Ramadas; Sundar Krishnasamy; Vidya Ravi; Atima Pathak; C. S. Devasena; Krishnan Swaminathan; Arunkumar Ganeshprasad; Ashok Ayyappa Kuppuswamy; Srinivasan Vedantham (Molecular and Cellular Biochemistry, 2022)

Molecular epidemiology of respiratory syncytial virus among children and adults in India 2016 to 2018 - Suresh S. Bandla; Santhosha Devadiga; Rushil Bhatt; Oliver C. Dsa; Arunkumar Govindakarnavar (Virus Genes, 2021)
Respiratory syncytial virus (RSV) is a common cause of respiratory tract infections among children less than 5 years of age and the elderly. This study intended to determine the circulating genotypes of RSV among severe acute respiratory illness (SARI) cases during the period 2016–2018 in India, among hospitalized acute febrile illness cases of age ranging from 1 to 65 years. Throat/nasopharyngeal swab samples were subjected for testing RSV and subgroups by real-time reverse transcriptase polymerase chain reaction (RT-PCR), further sequencing and phylogenetic analysis were performed for the second hypervariable region of the G gene. RSV-A and B subtypes co-circulated during the years 2016, 2017, and 2018, with RSV-A as the dominant subtype in 2016, and RSV-B as the dominant subgroup in 2017 and 2018. Phylogenetic analysis revealed that the circulating genotypes of RSV were GA2 (16/16), of RSV-A, and GB5 (23/23) of RSV-B in the South, North, and Northeast region of India during the period between 2016 and 2018. Here we report the first study comprising the distribution of RSV-A and B genotypes in the different geographic regions of India among children and adults during the year 2016 to 2018. We also report GA2.3.7 lineage of GA2 genotype for the first time in India to the best of our knowledge.

Hyperglycaemia cause vascular inflammation through advanced glycation end products/early growth response-1 axis in gestational diabetes mellitus - Barathi Rajaraman; Nirupama Ramadas; Sundar Krishnasamy; Vidya Ravi; Atima Pathak; C. S. Devasena; Krishnan Swaminathan; Arunkumar Ganeshprasad; Ashok Ayyappa Kuppuswamy; Srinivasan Vedantham (Molecular and Cellular Biochemistry, 2019)

The genetic architecture of tristyly and its breakdown to self‐fertilization - Ramesh Arunkumar; Wei Wang; Stephen I. Wright; Spencer C. H. Barrett (Molecular Ecology, 2017)
The floral polymorphism tristyly involves three style morphs with a reciprocal arrangement of stigma and anther heights governed by two diallelic loci ( S and M ). Tristyly functions to promote cross‐pollination, but modifications to stamen position commonly cause transitions to selfing. Here, we integrate whole‐genome sequencing and genetic mapping to investigate the genetic architecture of the M locus and the genetic basis of independent transitions to selfing in tristylous Eichhornia paniculata . We crossed independently derived semi‐homostylous selfing variants of the long‐ and mid‐styled morph fixed for alternate alleles at the M locus ( ssmm and ssMM , respectively), and backcrossed the F 1 to the parental ssmm genotype. We phenotyped and genotyped 462 backcross progeny using 1450 genotyping‐by‐sequencing (GBS) markers and performed composite interval mapping to identify quantitative trait loci (QTL) governing style‐length and anther‐height variation. A QTL associated with the primary style‐morph differences (style length and anther height) mapped to linkage group 5 and spanned ~13–27.5 Mbp of assembled sequence. Bulk segregant analysis identified 334 genes containing SNPs potentially linked to the M locus. The stamen modifications characterizing each selfing variant were governed by loci on different linkage groups. Our results provide an important step towards identifying the M locus and demonstrate that transitions to selfing have originated by independent sets of mating‐system modifier genes unlinked to the M locus, a pattern inconsistent with a recombinational origin of selfing variants at a putative supergene.

Genotyping of human adenoviruses circulating in Southwest India - C. Akhil; P. G. Suresha; S. Sabeena; M. Hindol; G. Arunkumar (VirusDisease, 2016)

Molecular and immunogenic characterization of BHK-21 cell line adapted CVS-11 strain of rabies virus and future prospect in vaccination strategy - Arunkumar C. Patel; Vikramaditya Upmanyu; Santhamani Ramasamy; Praveen Kumar Gupta; Rajendra Singh; Rabindra Prasad Singh (VirusDisease, 2015)

Characterization of mode of reproduction in Commiphora wightii [(Arnot) Bhandari] reveals novel pollen–pistil interaction and occurrence of obligate sexual female plants - K. A. Geetha; Aarti Kawane; Ashok Kumar Bishoyi; Arunkumar Phurailatpam; C. Ankita; S. K. Malik; R. Srinivasan; S. R. Bhat (Trees, 2013)